Meta- analysis: Base of Major Social Science Theories (Patan Prospective Journal, 2023)
Meta-analytic techniques in social science analysis are becoming increasingly relevant today. In this article, we will present how a meta-analysis method can be a useful base for sociologists. Different methods for meta-analysis, unique "concept-driven" literature searches. However, this search strategy may limit the researcher's ability to fully exploit the substantial body of pertinent research in fields with high theoretical diversity, such as social science. We tend to adopt a "beat-driven" strategy, where repetitive searches and updated computerized search techniques are used to find more publications cross disciplinary. This measure-based search approach is typically illustrated by two meta-analyses that look at how various social factors affect the all-cause mortality rate. A trend like imperialism might be a jumble of different perspectives on what humanity means. Imperialism, both political and economic, is occasionally mentioned. Imperialism is not limited to historical methods, political or economic facets. Instead, imperialism may be a collection of various human endeavors. To reach a conclusion, systematic reviews and meta-analyses combine the findings of various studies. While meta-analyses of applied scientific discipline analysis may run into practical issues due to the nature of the analysis domain, they are particularly useful for combining evidence to inform policy. Data from secondary sources were used to write this article.